2003
DOI: 10.1063/1.1622995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact statistics on electrical contact resistance

Abstract: Investigation of the skin effect in the bulk of electrical conductors with spin-polarized neutron radiographyThe flow of electrical current through a microscopic actual contact spot between two conductors is influenced by the flow through adjacent contact spots. A smoothed version of this interaction effect is developed and used to predict the contact resistance when the statistical size and spatial distribution of contact spots is known. To illustrate the use of the method, an idealized fractal rough surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Empirical relations have been established to connect the contact area and the thermal/electrical contact resistance [7]. A rigorous examination by Barber [8] proves the analogy between the conduction problem and the incremental elastic contact.…”
Section: Properties That Can Be Deduced From Rough Surface Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical relations have been established to connect the contact area and the thermal/electrical contact resistance [7]. A rigorous examination by Barber [8] proves the analogy between the conduction problem and the incremental elastic contact.…”
Section: Properties That Can Be Deduced From Rough Surface Contactmentioning
confidence: 99%
“…Scaling relations of the total contact area versus the applied load and roughness properties can be deduced [4], and compared with numerical simulations that have pre-specified spatial cutoff sizes [5,6]. We also discuss the validity conditions of predictions that are based on contact compliance, such as thermal/electrical contact resistance [7][8][9]. At microscale and nanoscale, it is worth noting that we still lack sufficient incorporation of micromechanics and novel deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of the possible physical origins of the factor of the approximate doubling in the resistance: A dielectric material (for dodecane, K = 2) confined within the contact is expected to raise the resistance by many orders of magnitude [6,31] and depend closely on the number of molecules confined within. It is possible that the molecules, being physisorbed and mobile, are not actually within the contacts but squeezed out into the regions immediately outside of them [46][47][48][49][50][51]. Indeed, Patton et al [3] reported that contact force of 200 lN is high enough to remove SAM molecules outside of MEMS contacts.…”
Section: Discussionmentioning
confidence: 94%
“…When load is increased, these plastically deformed spots join to form elastic spots [16]. The concept of fractal roughness has also been implemented to electrical [17] and thermal [18] contact resistances. Majumdar and Tien [18] developed a TCR model based on fractal characteristics of roughness and compared their model with experimental data.…”
Section: Why Plastic Microcontacts?mentioning
confidence: 99%